A Review of the Political Economy of Governance: From Property Rights to Voice - Keefer, Philip (World Bank, Washington, D.C., 2013)
Keefer reviews progress made in understanding the effects of different dimensions of governance on economic development, and the sources of good governance. The term governance has been used to embrace concepts that are heterogeneous both with respect to their effects on economic development and their genesis. Future progress in developing policy responses to bad governance will depend on separately examining these heterogeneous elements-the security of property rights, the quality of bureaucratic performance, corruption, voice, and accountability. Future progress will also depend on explicitly linking problems of governance to the overarching political environment and the incentives of governments to correct those problems.